Long-term clinical outcomes of tisagenlecleucel in patients with relapsed or refractory aggressive B-cell lymphomas (JULIET): a multicentre, open-label, single-arm, phase 2 study. Issue 10 (October 2021) - Schuster, Stephen J; Tam, Constantine S; Borchmann, Peter; Worel, Nina; McGuirk, Joseph P; Holte, Harald; Waller, Edmund K; Jaglowski, Samantha; Bishop, Michael R; Damon, Lloyd E; Foley, Stephen Ronan; Westin, Jason R; et al.
Summary: Background: In the primary analysis of the pivotal JULIET trial of tisagenlecleucel, an autologous anti-CD19 chimeric antigen receptor (CAR) T-cell therapy, the best overall response rate was 52% and the complete response rate was 40% in 93 evaluable adult patients with relapsed or refractory aggressive B-cell lymphomas. We aimed to do a long-term follow-up analysis of the clinical outcomes and correlative analyses of activity and safety in the full adult cohort. Methods: In this multicentre, open-label, single-arm, phase 2 trial (JULIET) done at 27 treatment sites in ten countries (Australia, Austria, Canada, France, Germany, Italy, Japan, the Netherlands, Norway, and the USA), adult patients (≥18 years) with histologically confirmed relapsed or refractory large B-cell lymphomas who were ineligible for, did not consent to, or had disease progression after autologous haematopoietic stem-cell transplantation, with an Eastern Cooperative Oncology Group performance status of 0–1 at screening, were enrolled. Patients received a single intravenous infusion of tisagenlecleucel (target dose 5 × 10 8 viable transduced CAR T cells). The primary endpoint was overall response rate (ie, the proportion of patients with a best overall disease response of a complete response or partial response using the Lugano classification, as assessed by an independent review committee) at any time post-infusion and was analysed in all patients who received tisagenlecleucel (the full analysis set). Safety was analysed in all patients who received tisagenlecleucel. JULIET is registered with ClinialTrials.gov, NCT02445248, and is ongoing. Findings: Between July 29, 2015, and Nov 2, 2017, 167 patients were enrolled. As of Feb 20, 2020, 115 patients had received tisagenlecleucel infusion and were included in the full analysis set. At a median follow-up of 40·3 months (IQR 37·8–43·8), the overall response rate was 53·0% (95% CI 43·5–62·4; 61 of 115 patients), with 45 (39%) patients having a complete response as their best overall response. The most common grade 3–4 adverse events were anaemia (45 [39%]), decreased neutrophil count (39 [34%]), decreased white blood cell count (37 [32%]), decreased platelet count (32 [28%]), cytokine release syndrome (26 [23%]), neutropenia (23 [20%]), febrile neutropenia (19 [17%]), hypophosphataemia (15 [13%]), and thrombocytopenia (14 [12%]). The most common treatment-related serious adverse events were cytokine release syndrome (31 [27%]), febrile neutropenia (seven [6%]), pyrexia (six [5%]), pancytopenia (three [3%]), and pneumonia (three [3%]). No treatment-related deaths were reported. Interpretation: Tisagenlecleucel shows durable activity and manageable safety profiles in adult patients with relapsed or refractory aggressive B-cell lymphomas. For patients with large B-cell lymphomas that are refractory to chemoimmunotherapy or relapsing after second-line therapies, tisagenlecleucel compares favourably with respect to risk–benefit relative to conventional therapeutic approaches (eg, salvage chemotherapy). Funding: Novartis Pharmaceuticals.